An in vitro study of the therapeutic effect of low laser treatment on induced ulcers - Balucas, Agiline
This paper will try to prove the effectivity of He:Ne lasers in the treatment of induced oral ulcers. Twelve rats were used and the oral lesions were induced by electrocautery. Treatment was dons in varying doses of 1 joule, 2 joules and 3 joules. The first group of rats was not treated and this is our control group. The second group was treated with 1 joule (15 seconds of laser treatment). The third group was treated with 2 joules (30 seconds) while the last group was treated with 3 joules (60 seconds), Two lesions were induced per rat. First dose of treatment was done right after inducing trauma. The second and the third treatment were done on the third and on the eighth day respectively. The lesions were observed clinically and histologically. Excisionai biopsies were done 24 hours after the first treatment, on the seventh day and on the fifteenth day. Clinical observation showed no significant difference in the hea1ing of lesions treated with laser against lesions without treatment. However, histologically, reduction in inflammatory reaction was seen on the lesions treated with the laser.